Abnormal cerebellar-prefrontal cortical pathways in obstructive sleep apnea with/without mild cognitive impairment - Shu, Yongqiang; Chen, Liting; Li, Kunyao; Li, Haijun; Kong, Linghong; Liu, Xiang; Li, Panmei; Xie, Wei; Zeng, Yaping; Peng, Dechang (Frontiers in Neuroscience, 2022)
Obstructive sleep apnea (OSA), a common respiratory sleep disorder, is often associated with mild cognitive impairment (MCI), which is a precursor stage to AD. However, the neuroimaging changes in patients with OSA with/without MCI are still under discussion. This study aimed to investigate the the temporal variability of spontaneous brain activity in OSA. Fifty-two OSA patients (26 with OSA with MCI (OSA-MCI) and 26 OSA without MCI (OSA-nMCI) and 26 healthy controls (HCs) underwent MRI scans and scale questionnaires. A dynamic amplitude of low-frequency fluctuation (dALFF) evaluation was performed to examine the time-varying nature of OSA-MCI and OSA-nMCI. Compared with OSA-MCI, OSA-nMCI had increased dALFF in the posterior cerebellar and right superior frontal gyrus; compared with HCs, increased dALFF was observed in the right posterior cerebellum of OSA-nMCI patients. A positive correlation between the bilateral posterior cerebellar lobes and right superior frontal gyrus was observed in OSA-MCI patients; however, in OSA-nMCI patients, a positive correlation was observed only between the bilateral posterior cerebellar lobes. The dALFF value of the left posterior cerebellar lobe was positively correlated with the apnea-hypopnea index, epworth sleepiness scale score, and arousal index in OSA-nMCIs ; while the dALFF value of the right posterior cerebellum was positively correlated with the apnea-hypopnea index and negatively correlated with the lowest oxygen saturation. This study argues that OSA-nMCIs and OSA-MCIs exhibit different temporal variabilities in dynamic brain functions, OSA-nMCIs may have variable intermediate states. we concluded that the functional abnormalities of the cerebellar-prefrontal cortex pathway in OSA-MCIs may cause cognitive impairment with OSA.